STRATEGI BUCK-PASSING NATO TERHADAP KEANGGOTAAN GEORGIA DI DALAM NATO TAHUN 2014 - Adita, Dila; ", M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research analyzes the strategies used North Atlantic Treaty Organization (NATO) to it’s partner countries, Georgia. After Georgia became independent from the Soviet Union, Georgia establish cooperation with the United States and targeting membership in NATO. At Bucharest Summit in 2008 NATO supports Georgia's aspirations to become a member of the alliance and will provide the status of the Membership Action Plan (MAP) to Georgia. But Georgia did not get MAP status at the time of NATO summit at Wales in 2014 ago. NATO only offers substantial cooperation package for Georgia (Substantial NATO-Georgia Package). This research will be analyzed with international system level of analysis. The strategy is explained within the framework of neorealism, the theory of buck-passing of great power politics and the concept of power. Based on the assumption of these theories, the security dilemma and distribution capabilities encourage great power to maintain its position in the face of potential threats from other great power. NATO tried to strengthen the political influence and security in the Eastern Europe and South Caucasus Region, because of the strategic position of Georgia which is located between the two regions. Security dilemma occurs because of the political and military expansion of Russia in the separatist region of Abkhasia and South Ossetia. The expansion of NATO in Eastern Europe Region has caused a potential threat to Russia even though the Cold War was over almost two decades.Keywords: Membership, Georgia, Substantial NATO-Georgia Package, Great Power Politics, Eastern Europe and South Caucasus Region, buck-passing, NATO.